INTERNAL STRUCTURE AND EXTERNAL RELATIONS EVIDENCE OF THE UCLA LONELINESS SCALE FOR APPLICATION TO INDONESIAN YOUNG WOMEN - Surijah, Edwin Adrianta; Nanik, Nanik (Faculty of Psychology, Universitas Diponegoro, 2023)
Evaluating one’s loneliness can yield significant benefits as it has been linked to numerous physical and mental health concerns. However, assessing loneliness faces difficulties due to inconsistent findings regarding its factorial structure. This study aims to investigate the internal structure evidence of the UCLA Loneliness Scale among Indonesian unmarried young adult women. A total of 318 participants completed the loneliness, well-being, extraversion, and neuroticism trait scales. Confirmatory factor analysis and bi-partial correlation were conducted to evaluate the validity evidence based on internal structure and relations to external variables. The results suggested that Model 2 (two correlated factors) is the best fit, χ 2 (151, n = 318) = 363.33, p = .000; CFI = .87, TLI = .85, RMSEA = .06, compared to other models tested (unidimensional & three factors). Also, UCLA-LS has two orthogonal structures consisting of favorable and unfavorable items (r = .83, p = .000; r = .72, p = .000, respectively) and negative correlations with well-being (r = -.42, p = .000) and extraversion (r = -.43, p = .000). Conversely, it correlates positively with the neuroticism subscale (r = .22, p = .000). This implies that perceived loneliness is unique among unmarried young adult women in Indonesia, and this scale may become a valuable tool to predict other widespread public health problems associated with loneliness